Dynamic Amplification of Bridge-Expansion-Joints considering Roughness induced Vehicle Vibrations. (2017) - Friedl, Roland; Mangerig, Ingbert
Abstract: The response of bridge expansion joints to the transient impact induced by crossing vehicles always represent the dynamic reaction of the former to the dynamic wheel contact forces at that particular moment. Separating the dynamic components in the vertical wheel contact forces, the dynamic amplification of the bridge expansion joints response, which is dominated by the driving velocity of the vehicle, its crossing position in lateral direction, the dynamic behavior of the expansion joint itself and most importantly by the interaction between the vehicle tire and the expansion joint's lamellas can be discussed. Due to the random distribution of the roughness amplitudes a stochastic characterization of the vehicle vibrations is necessary. In addition to the classical frequency approach based on complex transfer matrices completely describing the dynamic behavior of the vehicles and spectral density matrices characterizing the pavement roughness, the numerically efficient covariance analysis is applied. Therefore the spectral characteristics of the roughness amplitudes, which are described on the basis of multi-correlated random processes, are considered by introducing shaping filters in combination with a state space augmentation. The dynamic behavior of the considered bridge expansion joint is dominated by the properties of the discrete elastomeric spring elements. Hence a a non-proportional damping approach has to be applied to analyze the three dimensional finite element model of the structure using a modal superposition.